Arsenic in residential soil and household dust in Cornwall, south west England: potential human exposure and the influence of historical mining. Issue 4 (1st March 2017) - Middleton, Daniel R. S.; Watts, Michael J.; Beriro, Darren J.; Hamilton, Elliott M.; Leonardi, Giovanni S.; Fletcher, Tony; Close, Rebecca M.; Polya, David A.
Abstract : Exposure to arsenic (As) via residential soil and dust is a global concern, in regions affected by mining or with elevated concentrations present in underlying geology. Abstract : Exposure to arsenic (As) via residential soil and dust is a global concern, in regions affected by mining or with elevated concentrations present in underlying geology. Cornwall in south west England is one such area. Residential soil ( n = 127) and household dust ( n = 99) samples were collected from across Cornwall as part of a wider study assessing exposure to environmental As. Samples were analysed for total As (soil and dust samples) and human ingestion bioaccessible As (soil samples from properties with home-grown produce). Arsenic concentrations ranged from 12 to 992 mg kg −1 in soil and 3 to 1079 mg kg −1 in dust and were significantly higher in areas affected by metalliferous mineralisation. Sixty-nine percent of soils exceeded the 37 mg kg −1 Category 4 Screening Level (C4SL), a generic assessment criteria for As in residential soils in England, which assumes 100% bioavailability following ingestion. The proportion of exceedance was reduced to 13% when the bioavailability parameter in the CLEA model was changed to generate household specific bioaccessibility adjusted assessment criteria (ACBIO). These criteria were derived using bioaccessibility data for a sub-set of individual household vegetable patch soils ( n = 68). Proximity to former As mining locations was found to be a significant predictor of soil As concentration. This study highlights the value of bioaccessibility measurements and their potential for adjusting generic assessment criteria.